2014
DOI: 10.1093/bioinformatics/btu097
|View full text |Cite
|
Sign up to set email alerts
|

ZDOCK server: interactive docking prediction of protein–protein complexes and symmetric multimers

Abstract: The ZDOCK server is freely available to all academic and non-profit users at: http://zdock.umassmed.edu. No registration is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
1,149
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,472 publications
(1,161 citation statements)
references
References 17 publications
11
1,149
0
1
Order By: Relevance
“…suggestive of the presence of conserved ATP signaling via serpentine receptors in Plasmodium. These results were also confirmed using Z-Dock server online (Chen et al 2003;Pierce et al 2014) (data not shown). The identification of ATP binding site could be exploited for development of novel synthetic compounds.…”
Section: Molecular Dockingsupporting
confidence: 56%
“…suggestive of the presence of conserved ATP signaling via serpentine receptors in Plasmodium. These results were also confirmed using Z-Dock server online (Chen et al 2003;Pierce et al 2014) (data not shown). The identification of ATP binding site could be exploited for development of novel synthetic compounds.…”
Section: Molecular Dockingsupporting
confidence: 56%
“…Initial docking between the E. coli FrdA subunit of QFR (PDB code 1KF6) (24) and SdhE (PDB code 1X6I) (25) with both the distal N and C termini removed was performed using ZDOCK (26). Initial docking calculations constrained SdhE-R8, SdhE-M17, FrdA-M176, and FrdA-E460 as part of the binding surfaces.…”
Section: Expression and Purification Of The Hexahistidine Frdamentioning
confidence: 99%
“…24,[30][31][32][33][34][35] Roughly, there are two types of approaches: docking algorithms 30,31,35 whose goal is to predict the quaternary structure a priori and are template free, i.e., they do not require that any previous example of the quaternary structure be known. Others are template based 24,[32][33][34] and predict the interaction pose by copying from a related quaternary structure template.…”
Section: Introductionmentioning
confidence: 99%